A Review of Traumatic Axonal Injury following Whiplash Injury As Demonstrated by Diffusion Tensor Tractography - Jang, Sung Ho; Kwon, Young Hyeon (Frontiers in Neurology, 2018)
Whiplash is a bony or soft tissue injury resulting from an acceleration-deceleration energy transfer in the neck. Although patients with whiplash injury often complain of cerebral symptoms, and previous studies have reported evidence indicating brain injury, such an association has not been clearly elucidated. Traumatic axonal injury (TAI) is tearing of axons due to indirect shearing forces during acceleration, deceleration, and rotation of the brain or to direct head trauma. Diffusion tensor imaging (DTI) has an unique advantage to detect TAI in patients whose conventional brain CT or MRI results were negative following head trauma. Since the introduction of DTI, six studies using diffusion tensor tractography (DTT) based on DTI data have reported TAI in patients with whiplash injury, even though conventional brain CT or MRI results were negative. A precise TAI diagnosis in whiplash patients is clinically important for proper management and prognosis. Among the methods employed to diagnosis TAI in the six previous studies, the common diagnostic approach for neural tract TAI in individual patients with whiplash injury were: first, whiplash injury history due to car accident; second, development of new clinical symptoms and signs after whiplash injury; third, evidence of neural tract TAI in DTT results, mainly via configurational analysis; and fourth, coincidence of newly developed clinical manifestations and the function of injured neural tracts. All six studies were individual patient case studies; therefore, further prospective studies involving larger number of subjects should be encouraged.